Defining endogenous barcoding sites for CRISPR/Cas9-based cell lineage tracing in zebrafish. (20th February 2020) - Ye, Chang; Chen, Zhuoxin; Liu, Zhan; Wang, Feng; He, Xionglei
Abstract: There is a growing interest in developing experimental methods for tracking the developmental cell lineages of a complex organism. The recently developed CRISPR/Cas9-based barcoding method is, although highly promising, difficult to scale up because it relies on exogenous barcoding sequences that are engineered into the genome. In this study, we characterized 78 high-quality endogenous sites in the zebrafish genome that can be used as CRISPR/Cas9-based barcoding sites. The 78 sites are all highly expressed in most of the cell types according to single-cell RNA sequencing (scRNA-seq) data. Hence, the barcoding information of the 78 endogenous sites is recovered by the available scRNA-seq platforms, enabling simultaneous characterization of cell type and cell lineage information.